Cobalt‐60 tomotherapy: Clinical treatment planning and phantom dose delivery studies. Issue 8 (22nd July 2013) - Dhanesar, Sandeep; Darko, Johnson; Joshi, Chandra P.; Kerr, Andrew; John Schreiner, L.
Abstract : Purpose: : Investigations have shown that a Cobalt‐60 (Co‐60) radioactive source has the potential to play a role in intensity modulated radiation therapy (IMRT). In this paper, Co‐60 tomotherapy's conformal dose delivery potential is evaluated by delivering conformal dose plans on a cylindrical homogeneous phantom containing clinical structures similar to those found in a typical head and neck (H&N) cancer. Also, the clinical potential of Co‐60 tomotherapy is investigated by generating 2D clinical treatment plans for H&N and prostate anatomical regions. These plans are compared with the 6 MV based treatment plans for modalities such as linear accelerator‐based tomotherapy and broad beam IMRT, and 15 MV based 3D conformal radiation therapy (3DCRT). Methods: : For experimental validation studies, clinical and nonclinical conformal dose patterns were delivered on circular, homogeneous phantoms containing GafChromic film. For clinical planning study, dose calculations were performed with the EGSnrc Monte Carlo program, where a Theratronics 780C Co‐60 unit and a 6 MV linear accelerator were modeled with a MIMiC binary multileaf collimator. An inhouse inverse treatment planning system was used to optimize tomotherapy plans using the same optimization parameters for both Co‐60 and 6 MV beams. The IMRT and 3DCRT plans for the clinical cases were generated entirely in the Eclipse treatment planning system based on inhouse IMRT and 3DCRT site specific protocols. Results: : The doses delivered to the homogeneous phantoms agreed with the calculations, indicating that it is possible to deliver highly conformal doses with the Co‐60 unit. The dose distributions for Co‐60 tomotherapy clinical plans for both clinical cases were similar to those obtained with 6 MV based tomotherapy and IMRT, and much more conformal compared to 3DCRT plans. The dose area histograms showed that the Co‐60 plans achieve the dose objectives for the targets and organs at risk. Conclusions: : These results confirm that Co‐60 tomotherapy is capable of providing state‐of‐the‐art conformal dose delivery and could be used for the treatment of targets in both small and larger separation anatomical regions.